Impact Of Business Cycle And Revenue Diversification On Capital Buffer And Bank Risk: Empirical Studies From Asean Countries - Muhammad Ridho Sahputra; Mohamad Adam; Muizzuddin Muizzuddin; Isnurhadi Isnurhadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this research is to examine how business cycle and income diversification affect on capital buffer and banking risk in ASEAN from 2020 to 2022. The samples used in this research were 93 banks taken using purposive sampling techniques in the Philippines, Indonesia, Malaysia, Singapore, Thailand, and Vietnam. By using 2-SLS on panel data to analyze the data in the model being built. This research found that when the economy is in a contraction phase, banks will increase capital buffers. Then, if the bank’s revenue streams become more diversified, this could potentially weaken its capital buffer reserves and decrease risk levels in the banking sector. Meanwhile, expansionary business cycles and revenue diversification provide in reducing bank risk to encourage economic growth. In addition, the correlation between the level adjustment of capital buffer and bank risk confirms a positive impact.